With eyes and ears open
1 online resource.
Keywords: In With Eyes and Ears Open: The Role of Visitors in the Society of Jesus , twelve historians examine important visitations in the history of the Society. After a thorough investigation of the nature and role of the “visitor” in Jesuit rules and regulations, ten visitations of missions and provinces—from Peru in the sixteenth century, to Ireland in the seventeenth, to the Zambesi mission and Australia in the twentieth—are considered. Visitors, appointed by the superior general in Rome, surveyed the situation for fidelity to the Jesuit way of life, resolved any problems, and recommended future paths, often to the disapproval of Jesuit hosts. One contribution concerns the canonical visitation of the non-Jesuit Francis Saldanha da Gama in 1758, which resulted in the expulsion of the Jesuits from Portugal in 1759.